SUSTAINABLE DEVELOPMENT AS A FACTOR IN STRUCTURAL IMBALANCES IN THE UKRAINIAN ECONOMY - IVANCHENKOV, Viacheslav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to studying structural imbalances of the Ukrainian economy in the context of sustainable development. It is determined that the domestic economy has been formed for a long time with deep structural imbalances. Its excessive dependence on raw materials industries, low level of innovation, and significant regional disparities inhibit its development and make it vulnerable to external challenges. These distortions create problems that manifest themselves in low rates of economic growth, deepening social inequality, increasing unemployment, and aggravating environmental difficulties. In addition, they limit the country’s investment potential, as investors are often reluctant to invest in unstable and unpredictable economic conditions. It is proven that sustainable development is not just a desirable concept but a critical necessity and the main task for Ukraine. It offers a comprehensive approach that allows rethinking traditional economic models that ignore long-term environmental and social consequences for quick profit. Instead of a confrontation between economic growth and environmental protection, sustainable development offers a path to harmony and mutually beneficial coexistence. It is established that the key tool for overcoming existing imbalances is the implementation of the principles of sustainable development, which includes economic diversification, the development of innovative and high-tech industries, the transition to renewable energy sources, and a circular economy. It will create a more stable, competitive, and inclusive economy, ensuring long-term prosperity and a high quality of life for all citizens of Ukraine. It is substantiated that integrating the principles of sustainable development into all spheres of economic life is not just a desirable direction but a strategic imperative for Ukraine. This is the only way to build a balanced and prosperous future.